Asas Keadilan Dalam Perspektif Penetapan Ganti Rugi Pembebasan Tanah Untuk Kepentingan Umum - Isye Junita Melo (Universitas Negeri Manado, 2022)
The issue of land, revocation of rights or land acquisition always involves two dimensions that must be placed in a balanced way, namely